Standardization Of Galamai Recipes As Traditional Food In Nagari Bukik Sikumpa, Fifty City District, West Sumatera - Khair, Dillatul; Gusnita, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
Differences in the selection of materials, the measurement of ingredients and the techniques for making galamai make the resulting quality different. Basically, the technique for making galamai is glutinous rice flour cooked with coconut milk using cane sugar or palm sugar using a very large cauldron. This study aims to describe the standardization of the recipe, the method of preparation and the quality of galamai in Nagari Bukik Sikumpa, Lima Puluh Kota District. This type of research is qualitative and quantitative research using mixed methods (Mixed Method). The data in this study uses primary data. Qualitative data collection techniques are observation, interviews, documentation and quantitative data collection techniques are organoleptic test questionnaire formats. Qualitative data analysis techniques use three streams of activity, namely: data reduction, data presentation, drawing conclusions and quantitative data analysis techniques using the formula (Mx=∑ x / N), data validity testing the validity of qualitative data, namely: extension of participation, diligent observation, and triangulation. Based on the results of the study, 3 galamai recipes were obtained. The results of the organoleptic test obtained the highest score by Mr. Ahmad Robianza from Jorong Padang Belimbing with an average value of 19.6. The standardization of the galamai recipe was carried out by organoleptic tests to obtain good galamai quality including: galamai shape (neat and uniform), galamai color (dark brown), galamai aroma (fragrant), galamai texture (chewy) and galamai taste (sweet).